Implementation of DWSIM simulator and its effectiveness as alternative simulation software for chemical engineering students / Muhammad Azri Khashim - Khashim, Muhammad Azri; Azian Rohaidi, Dina Edryana; Abd Rauf, Madihah; Fissol, Nor Farisha Mastura
Computer simulation makes an important contribution in chemical process design. Currently, there are many types of commercial software that are available in the market for simulation of chemical processes such as Aspen HYSYS and Aspen Plus. However, these commercial software are expensive and their license need to be renewed every year that might put a financial pressure especially on institutions or universities with tight budget constraints. Due to this situation, certain parties had developed open-source simulation software, which are freely accessible, for the use of studying, reviewing, and conducting modifications on chemical engineering processes. Questions arise whether this free software could produce simulation results as accurate as the commercial software. One such software is DWSIM simulator which is being investigated in this project. In this study, various steady-state process simulations were conducted using DWSIM simulator to assess the viability of this simulator as a potential alternative software to be used in certain chemical engineering subjects by evaluating the accuracy of its simulation results. This was done by simulating several steady-state processes that were commonly found in Chemical Engineering syllabus such as Materials and Energy Balances and the simulation results were then compared to those obtained by Aspen Plus and Aspen HYSYS. It was found that the disparity between the commercial software and DWSIM is great. It is agreed that the accepted percentage error is not more than 5% [1]. This is because the percentage error obtained from this study is inconsistent. It has been proved that, DWSIM simulator can be used to perform a simulation but it requires further improvement to be implemented in the chemical engineering syllabus.